2015
DOI: 10.1038/nphoton.2014.322
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustically guided wavefront shaping for enhanced optical focusing in scattering media

Abstract: Non-invasively focusing light into strongly scattering media, such as biological tissue, is highly desirable but challenging. Recently, ultrasonically guided wavefront shaping technologies have been developed to address this limitation. So far, the focusing resolution of most implementations has been limited by acoustic diffraction. Here, we introduce nonlinear photoacoustically guided wavefront shaping (PAWS), which achieves optical diffraction-limited focusing in scattering media. We develop an efficient dua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
256
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 293 publications
(257 citation statements)
references
References 37 publications
1
256
0
Order By: Relevance
“…As discussed earlier, in photoacoustic effect, transient photon energy-no matter it is ballistic or diffusive-is absorbed by tissue molecules and converted into much less scattering ultrasonic waves, which can be detected using a single or a series of transducers. The detected signal can be generally expressed by [48]:…”
Section: Photoacoustically-guided Wavefront Shaping (Paws)mentioning
confidence: 99%
See 4 more Smart Citations
“…As discussed earlier, in photoacoustic effect, transient photon energy-no matter it is ballistic or diffusive-is absorbed by tissue molecules and converted into much less scattering ultrasonic waves, which can be detected using a single or a series of transducers. The detected signal can be generally expressed by [48]:…”
Section: Photoacoustically-guided Wavefront Shaping (Paws)mentioning
confidence: 99%
“…For example, it has been demonstrated that subacoustic diffraction-limited optical focusing is possible when the detected PA signals (which are broadband) are spectrally filtered and then used as the feedback [26,45]. From the perspective of generation nonlinearity, Lai et al developed a dual-pulse excitation approach (Figure 3a), firing two consecutive, yet identical, optical pulses to generate two individual PA signals-the difference between them create a nonlinear PA response that can be used as a nonlinear feedback [48]. The hypothesis was built upon a so-called Grueneisen effect [49].…”
Section: Photoacoustically-guided Wavefront Shaping (Paws)mentioning
confidence: 99%
See 3 more Smart Citations